Measurement of τ polarization in W→τν decays with the ATLAS detector in pp collisions at [Formula: see text]. - Aad, G; Abbott, B; Abdallah, J; Abdel Khalek, S; Abdelalim, A; Abdesselam, A; Abdinov, O; Abi, B; Abolins, M; AbouZeid, O; Abramowicz, H; Abreu, H; et al. (2012)
In this paper, a measurement of τ polarization in W→τν decays is presented. It is measured from the energies of the decay products in hadronic τ decays with a single final state charged particle. The data, corresponding to an integrated luminosity of 24 pb(-1), were collected by the ATLAS experiment at the Large Hadron Collider in 2010. The measured value of the τ polarization is [Formula: see text], in agreement with the Standard Model prediction, and is consistent with a physically allowed 95 % CL interval [-1,-0.91]. Measurements of τ polarization have not previously been made at hadron colliders.